(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: This scientific article aims to describe the knowledge and practices related to the food safety of cooks and some related factors in the communal kitchens of preschools in Ha Tinh City in 2022. Research Methodology: We used a cross-sectional descriptive study design to conduct our research, was conducted on 110 research subjects who were food processors or involved in food processing stages at the communal kitchens of preschools. The knowledge and practice of food processors are assessed according to a set of questions and observation checklists built based on decision number: 37/QD-ATTP issued in 2015. Data entry and analysis above two software Epidata 3.1 and Stata 16, using descriptive statistics of frequency (n) and ratio (%), Chi-square test to find the difference with significance level α = 0.05. Results: The proportion of food handlers with general knowledge of food safety was 70.9%, and the proportion of food handlers with the correct general practice of food safety was 60.9%. Factors related to the knowledge of food handlers include high school education level (OR=5.4; 95%CI: 1.3 - 22.2; p=0.019) and current position in the kitchen as a head cook (OR=4.3; 95%CI: 1.3 - 14.3; p=0.040). Similarly, these were also two factors related to the practice of food handlers (high school education level (OR=4.2; 95%CI: 1 - 16.7; p=0.044) and current position as head cook in the kitchen (OR=3.5; 95%CI: 1 - 11.9; p=0.050)). Conclusion: The overall rate of knowledge and practice regarding food safety of cooks in communal kitchens of preschools was found to be quite good. The cooks ‘ educational level and job position in the kitchen were two statistically significant factors associated with their knowledge and practices regarding food safety.